A basic fertilizer recommendation schedule for sugarcane in the western sugarcane belt of Thailand - Sruttaporn, C. (The Malaysian Society of Soil Science, 2014)
Much of the sugarcane in the western sugarcane belt of Thailand is cultivated on flat, clay loam soil (Kamphaeng Saen Series: Hydromorphic non calcic brown soil). Approximately 22520 tonnes of nitrogen fertilizer, 6802 tonnes of phosphorus fertilizer and 8092 tonnes of potassium fertilizer are applied annually to the sugarcane crop in this area.The fertilizer recommendations by the department of Agriculture are usually based on the results of fertilizer trials and the product available in the local market.The results of 60 fertilizer trials carried out from 1987 to 1991 are presented in this paper.Most of the trials were conducted in sugarcane fields under irrigated and non-irrigated conditions.N,P and K application rates were varied and cane yield, sugar yield, sugar content and agronomic characteristics were used to determine the most suitable rates of fertilizer application.Results of the experiments indicates the fertilizer recommendation rate varied depends on the growing zone (irrigated and rainfed) and nature of the cane (plant and ratoon).Economic considerations based on cane and fertilizer price are also presented.Fertilizer usage by canegrowers, particularly the small farms, was generally found to be lower than that recommended by the Department of Agriculture.